ANIE'S CHILDHOOD TRAUMA AND PSYCHOPATHY BEHAVIOUR IN LUCINDA BERRY’S NOVEL "THE PERFECT CHILD" - Wibisono, Yusriya; Pandin, Moses Glorino Rumambo (Airlangga Development Journal, 2024)
This research aims to analyze the connection between childhood trauma and the behavior of one of the characters, Janie, in The Perfect Child novel by Lucinda Berry. This study employed a qualitative method and used Sigmund Freud's psychoanalysis theory to obtain a deeper understanding, particularly the defense mechanisms and the tripartite model (id, ego, and superego). The study finds that there is an imbalance in Janie's personality structure that was caused by her childhood trauma, in particular, abuse and neglect that have been done by her birth mother, Becky. Thus, Janie's trauma triggered her psychological behavior, which tends to refer to signs of a child at risk of psychopathy, such as; aggression towards animals or pets, cheating on friends or enemies, or individuals who are neutral and bullying other children. Subsequently, due to Janie's trauma of her birth mother, she defends herself around women. Especially those who resemble mother figures.